Perbedaan Persepsi Antara Sebelum Dan Sesudah Diberikan Informational Support Pada Pasien Diabetes Mellitus Di Ruang Rawat Inap RSUD DR.Moewardi - NURSITA, Fathima; , Arum Pratiwi, S.Kp., M.Kes; , Vinami Yulian, S.Kep., Ns., M.Sc (2015)
DM was a disease that can not be cured, so that a person with diabetes tend to have a negative perception of the disease. One's perception of a disease associated with a person's compliance in carrying out the treatment. Negative perception of the disease raises a person's unhappiness resulting reluctant to make care and treatment. Positive perception of a person against a disease that makes people willing to undergo treatment and the treatment itself routinely and regularly. Informational support was an act to increase the patient's perception of the disease in the form of provision of advice, ideas and information. This study aims to analyze existing differences in perception between Before and After Awarded Informational Support in Patients with Diabetes Mellitus in Space Inpatient Hospital Dr. Moewardi. The study population was patients with DM who underwent hospitalization in hospitals. Dr. Moewardi with a sample of 33 patients. Gathering data using questionnaires and analyzed using paired samples t-test. The study concluded that (1) the perception before giving informational support mostly positive, (2) the perception after giving informational support all positive, and (3) there are differences in perception of the difference between before and after Given Informational Support in Patients with Diabetes Mellitus in patient wards Hospital Dr. Moewardi.